BIOSMART Agri-environmental policy, silvopastoral systems, biodiversity, and climate change - Escobar, María Paula; Barnes, Andrew P.; Garratt, Michael; Kinneen, Lois; Rosique Esplugas, Cristina; Sepúlveda, Ignacio; Thompson, Jill; Quintero, Marcela; Romero Sánchez, Miguel Antonio (2021)
BIOSMART1 is a 3-year interdisciplinary and international project focused on studying the implementation of silvopastoral systems (SPS)2 and other agrienvironmental schemes in the Colombian Amazon for the benefit of society, the environment, and the local economy. These schemes include the Sustainable Amazonian Landscapes project led by CIAT.3 Our methods include semi-structured interviews, telephone surveys, focus groups, risk-perception games, land-use change modeling, and ecological fieldwork. Our aims are to improve understanding of these systems to support sustainable development goals around eradication of poverty, boosting rural development, achieving net-zero carbon farming, and conserving forests and biodiversity.